2017
DOI: 10.1161/jaha.117.006510
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Cholinergic Anti‐Inflammatory Pathway in Rat With Ischemic Cardiomyopathy–Modified Electrophysiological Function of Heart

Abstract: BackgroundWith chronic ischemia after myocardial infarction, the resulting scar tissue result in electrical and structural remodeling vulnerable to an arrhythmogenic substrate. The cholinergic anti‐inflammatory pathway elicited by vagal nerve via α7 nicotinic acetylcholine receptors (α7‐nAChR) can modulate local and systemic inflammatory responses. Here, we aimed to clarify a novel mechanism for the antiarrhythmogenic properties of vagal nerve during the ischemic cardiomyopathy (ICM).Methods and ResultsLeft an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…In recent decades, studies have shown that CAP induction by vagus nerve stimulation or an α7nAChR agonist reduces inflammation and improves disease states, and inhibiting CAP promotes inflammatory responses and aggravates diseases [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, studies have shown that CAP induction by vagus nerve stimulation or an α7nAChR agonist reduces inflammation and improves disease states, and inhibiting CAP promotes inflammatory responses and aggravates diseases [30].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, studies have shown that CAP induction by vagus nerve stimulation or an α7nAChR agonist reduces inflammation and improves disease states, and inhibiting CAP promotes inflammatory responses and aggravates diseases [ 30 ]. Additionally, investigators found that the spleen is vitally important to inhibit systemic inflammatory response by α7nicotinic agonists or vagus never stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse was positioned on a heating pad to maintain body temperature at 37°C and anesthetized by inhaling isoflurane. The echocardiographic ventricular structure was visualized by a blinded investigator in the left parasternal long-axis view, and the left systolic function (LVEF) was measured as previously described [ 20 ]. Other parameters, including the left ventricular (LV) posterior wall end-diastolic and end-systolic thickness, interventricular septal end-diastolic and end-systolic thickness, LV end-diastolic and end-systolic diameter, LV end-diastolic and end-systolic volume, and LV fractional shortening were also measured.…”
Section: Methodsmentioning
confidence: 99%
“…Initial reports of the cholinergic anti-inflammatory pathway in the cardiovascular system for clinical use investigated the protective effects of vagus nerve stimulation (VNS) in rats, dogs, rabbits, and pigs in chronic heart failure (Ando et al 2005;Calvillo et al 2011;Hamann et al 2013;Nuntaphum et al 2018;Uemura et al 2010;Vaseghi et al 2017). VNS demonstrated a wide range of effects on the heart following injury, including anti-arrhythmogenic effects following ischemia in rats and rabbits (Ando et al 2005;Brack et al 2011;Wu et al 2017), reduced inflammation and infarct size (Calvillo et al 2011;Wu et al 2017), prevention of remote vascular disfunction (Zhao et al 2013), improved redox status after MI (Shinlapawittayatorn et al 2014;Tsutsumi et al 2008), and has been demonstrated to be tolerable in humans with some efficacy in advanced heart failure states (Klein and Ferrari 2010;Schwartz et al 2008).…”
Section: Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%